2020
DOI: 10.1186/s41065-020-00151-z
|View full text |Cite
|
Sign up to set email alerts
|

Microarray data analysis reveals gene expression changes in response to ionizing radiation in MCF7 human breast cancer cells

Abstract: Background The aim of this study was to identify potential therapeutic target genes for breast cancer (BC) by the investigation of gene expression changes after ionizing radiation (IR) in BC cells. Gene expression profile GSE21748, including BC cell line MCF-7 samples at different time points after IR treatment, were downloaded from Gene Expression Omnibus. Differentially expressed genes (DEGs) were identified in different time points following IR compared with cell samples before IR, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Forkhead box D1 (FOXD1), a member of the Forkhead family, was first identified in the forebrain neuroepithelium and has been demonstrated to be a vital gene participating in the development of the kidney and retina [ 4 ]. Previous studies have shown that FOXD1 also participates in the development of various cancers, including liver cancer [ 5 ], cervical cancer [ 6 ], pancreatic cancer [ 7 ], breast cancer [ 8 ], and glioma [ 9 ]. For instance, Sun et al found that lncRNA NORAD promotes cell stemness and angiogenesis in liver cancer by regulating the miR-211-5p/FOXD1/VEGF-A axis [ 5 ]; Cheng et al found that FOXD1 can determine the renewal ability and tumorigenicity of glioma through transcriptional regulation of ALDH1A3 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forkhead box D1 (FOXD1), a member of the Forkhead family, was first identified in the forebrain neuroepithelium and has been demonstrated to be a vital gene participating in the development of the kidney and retina [ 4 ]. Previous studies have shown that FOXD1 also participates in the development of various cancers, including liver cancer [ 5 ], cervical cancer [ 6 ], pancreatic cancer [ 7 ], breast cancer [ 8 ], and glioma [ 9 ]. For instance, Sun et al found that lncRNA NORAD promotes cell stemness and angiogenesis in liver cancer by regulating the miR-211-5p/FOXD1/VEGF-A axis [ 5 ]; Cheng et al found that FOXD1 can determine the renewal ability and tumorigenicity of glioma through transcriptional regulation of ALDH1A3 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, microarray analysis demonstrated that STAT1 is co-expressed with ESCO2 and may regulate its transcription in breast cancer [24]. These ndings indicate a positive regulatory loop in which STAT1 increases ESCO2 expression, which further activates STAT1.…”
Section: Discussionmentioning
confidence: 94%
“…So far, our data have indicated that ESCO2 depletion signi cantly suppressed tumor growth in vitro and in vivo. In addition, a recent bioinformatics study indicated the potential signi cance of the STAT1/ESCO2 pathway in breast cancer [24]. It is reasonable to speculate that STAT1 may also be involved in ESCO2-associated tumorigenesis in HPC.…”
Section: Stat1-overexpression Suppressed Esco2-de Ciencymediated Tumo...mentioning
confidence: 98%
“… 30 Bai et al , revealed identified potential therapeutic target genes for breast cancer (BC) by the investigation of gene expression changes after ionizing radiation (IR) in BC cells, and found FOXD1 was one of the hub nodes in the transcriptional regulatory network of the overlapping DEGs. 31 Another bioinformatics analysis also revealed FOXD1 was the breast cancer survival related gene. 32 Zhao et al reported that FOXD1 was up-regulated in breast cancer tissues, and depletion of FOXD1 expression decreases the ability of cell proliferation and chemoresistance in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%